Approach and decisions in cholesteatoma: a literature review - Fandiño Cardenas, Marcela (2023)
Cholesteatoma is a soft-looking, compressible mass mainly associated with hypoacusis. Its diagnosis is made by otoscopy, but if the physical examination is not conclusive, radiological studies should be performed. Its presentation is infrequent; thus, the incidence of acquired cholesteatoma per year in Colombia is 3/100000 children and 9.2/100000 adults. It is important in the evaluations that each health personnel can recognize it and refer it, allowing early surgical intervention to avoid invasive clinical pictures that can increase the possibility of complications. Our objective was to describe the importance of cholesteatoma with its clinical implications in different patients with auditory pathology, which allows to understand the importance of timely diagnosis. A literature search was performed in PubMed and Scielo databases, oriented towards updated and relevant articles in English and Spanish, published in the last 5 years.  The relationship between hypoacusis  and cholesteatoma, its medical importance, implications and therapeutic approach were analyzed. Different studies show the presence of cholesteatoma and unilateral hypoacusis, in some cases the clinical presentation is associated to syndromic pathologies. In this pathology the treatment is surgical, with a previous evaluation that establishes the type of intervention, additionally, the post-surgical follow-up is mandatory in all patients. In conclusion, cholesteatoma is a cause of hypoacusis, especially in the pediatric population, which must be diagnosed in a timely manner in order to allow a specialized assessment that ffers a surgical treatment according to the anatomical compromise and individualization of the patient.